Randomized controlled trial comparing 35% trichloroacetic acid peel and 5‐aminolaevulinic acid photodynamic therapy for treating multiple actinic keratosis. (1st May 2017) - Holzer, G.; Pinkowicz, A.; Radakovic, S.; Schmidt, J.B.; Tanew, A.
Summary: Background: Photodynamic therapy (PDT) and chemical peels with trichloroacetic acid (TCA) can be applied to large skin areas and thus are suitable treatment options for patients with multiple actinic keratosis (AK). However, despite its long use, TCA has been investigated only rarely in this indication. Objectives: This randomized, observer‐blinded, intrapatient comparative study sought to investigate the efficacy and safety of 35% TCA vs. aminolaevulinic acid 20% (ALA) PDT in patients with extensive field cancerization and multiple AKs in the face or on the scalp. Methods: Twenty‐eight patients with at least five AKs in two comparable anatomical areas on the head were treated with 35% TCA and ALA PDT randomly assigned to each area. Their therapeutic efficacy, adverse events and cosmetic outcome were assessed by a blinded investigator at 1, 3, 6 and 12 months after treatment. Results: After 12‐months' follow‐up TCA and ALA PDT reduced the total lesion count, the primary outcome, by 31% and 58%, respectively ( P = 0·006). Complete clearance of pre‐existing AKs were 49% for TCA and 74% for ALA PDT ( P = 0·011). Treatment failure (number of AKs greater than 50% of the baseline count) was observed in seven patients (25%) after TCA and in two patients (7%) after PDT treatment. Treatment‐related pain was significantly higher for ALA PDT (visual analogue scale 7·5 ± 2·3 vs. TCA: 5·1 ± 2·6; P = 0·04), whereas scarring ( n = 6, 21%) was seen only in TCA treated patients. Conclusions: ALA PDT provided better clinical results than TCA in the treatment of patients with extensive field cancerization and multiple AKs.